Effects of Return on Asset, Debt to Asset Ratio, Current Ratio, Firm Size, and Dividend Payout Ratio on Firm Value - Husna, Asmaul; Satria, Ibnu (International Journal of Economics and Financial Issues, 2019)
The purpose of the research is to determine the effect of return on assets, debt to asset ratio, current ratio, firm size, and dividend payout ratio to the firm value of manufacturing companies listed in Indonesia Stock Exchange for the period 2013-2016. The sampling method was purposive sampling techniques and obtained from 32 samples out of 138 firms that met the criteria. The analysis technique applied was a multiple regression analysis. The research found that the return on asset and firm size have effects on firm value, debt to asset ratio, current ratio, and dividend payout ratio, but do not affect firm value. This paper shows that return on asset has an effect firm value, debt to asset ratio does not effects firm value, firm size has an effect firm value, and payout ratio has no effect on firm value. Keywords: Firm Value, Return on Assets, Debt to Asset Ratio, Current Ratio, Firm Size, and Dividend Payout Ratio JEL Classifications: E10, E32, E60 DOI: https://doi.org/10.32479/ijefi.8595